2015
DOI: 10.1002/jbmr.2605
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Reference Point Microindentation Complements Clinical Measures for Improved Fracture Risk Assessment at the Human Femoral Neck

Abstract: In contrast to traditional approaches to fracture risk assessment using clinical risk factors and bone mineral density (BMD), a new technique, reference point microindentation (RPI), permits direct assessment of bone quality; in vivo tibial RPI measurements appear to discriminate patients with a fragility fracture from controls. However, it is unclear how this relates to the site of the most clinically devastating fracture, the femoral neck, and whether RPI provides information complementary to that from exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Other report revealed that cortical porosity is not superior to BMD determined by DXA hofr identification of HD patients with fragility fracture [133]. Moreover, clinical assessment of human femoral mechanical properties by reference point indentation (RPI), which is a novel technique that allows direct measurement of bone material or biomechanical properties, indicated that BMD did not discriminate fracture cases form controls [134]. These recent studies suggest that bone strength in CKD patients may be affected by many factors in a complicated manner, and the major factor and its degree of contribution remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Other report revealed that cortical porosity is not superior to BMD determined by DXA hofr identification of HD patients with fragility fracture [133]. Moreover, clinical assessment of human femoral mechanical properties by reference point indentation (RPI), which is a novel technique that allows direct measurement of bone material or biomechanical properties, indicated that BMD did not discriminate fracture cases form controls [134]. These recent studies suggest that bone strength in CKD patients may be affected by many factors in a complicated manner, and the major factor and its degree of contribution remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Jenkins et al[66] undertook cRPI measurements (10 cycles up to 10 N) on femoral neck samples collected at surgery after low-trauma hip fracture (interquartile range 77–87 yo, n=46 with 17 males) and from cadaveric controls (interquartile range 61–74 yo, n=16 with 7 males). Again, bone from osteoporotic fracture patients was less resistant to microindentation than bone from controls, even after adjusting for cofounding factors (age, sex, BMI, and height).…”
Section: Osteoporosis-related Differences In Indentation-derived Mechmentioning
confidence: 99%
“…Preclinical results also support the effectiveness of treatments on RPI properties, independently of BMD changes [47]. [48] for cyclic microindentation, but must also be studied for the impact microindentation tests appropriate for clinical use.…”
Section: Accepted M Manuscriptmentioning
confidence: 80%